Comprehensive analysis of economic, sociocultural, and environmental impacts on community well-being in tourist areas - Saputra, Hijrah; Madyawati, Sri Pantja; Wijoyo, Suparto; Megasari, Ni Luh Ayu (Privietlab, 2025)
Tourism exerts a multidimensional influence on the well-being of communities in destination areas, encompassing economic, sociocultural, and environmental dimensions. This study aims to identify the key factors contributing to local community well-being and evaluate whether dependence on tourism has a measurable effect. A quantitative approach was employed using structured surveys involving 398 respondents from Karang Sidemen Village, Bali. Data were analyzed using descriptive statistics, Pearson’s correlation, multiple linear regression, and independent t-tests. The findings reveal that the economic impact is perceived as the most substantial contributor to well-being, followed by sociocultural and environmental aspects. The regression results indicate that economic, sociocultural, and environmental factors exert an equally significant influence (β = 0.333), whereas community attitudes, behavioral involvement, and tourism dependency show no statistical significance. Additionally, no significant difference in well-being was found between individuals reliant on tourism and those with alternative livelihoods (p = 0.506). These results underscore the importance of equitable and sustainable tourism development policies, emphasizing inclusive economic benefit distribution, cultural preservation, and responsible environmental management to ensure long-term community well-being and sustainability.